Exploring broilers and native fowls of Andaman and Nicobar Islands as a source of β-lactamase-producing Enterobacteriaceae even with limited anthropogenic activities and docking-based identification of catalytic domains in novel β-lactamase variants - Bhowmick, Sneha; Pal, Surajit; Sunder, Jai; Sujatha, T.; De, Arun Kumar; Mondal, Tousif; Singh, Abhishek D.; Joardar, Siddhartha Narayan; Batabyal, Kunal; Dutta, Tapan Kumar; Bandyopadhyay, Samiran; Tiwari, Ananda; et al. (Frontiers in Veterinary Science, 2023)
Objectives: The present study was conducted to detect the occurrence of beta-lactamase and biofilm-producing-Escherichia coli, Salmonella and Klebsiella in broilers and native fowl reared in Andaman and Nicobar Islands, India. The study also included molecular docking experiments to confirm the nature of the catalytic domains present in β-lactamase variants obtained and to reveal clonal relationship of the isolates with human clinical strains from the database. Results : In total, 425 Enterobacteriaceae strains were isolated form the collected samples. Klebsiella (42.58%) was found to be the most prevalent, followed by Salmonella (30.82%) and E. coli (26.58%). Phenotypical antibiogram of all the 425 isolates showed highest resistance against oxytetracycline (61%-76%) and the lowest against gentamicin (15%-20%). Phenotypical production of β-lactamase enzymes was observed in 141 (33.38%) isolates. The isolation rate of beta-lactamase producing E. coli, Salmonella and Klebsiella was significantly more (p<0.05) in the birds reared in South Andaman district (25.6%, 17.5%, 18.7%, respectively) than Nicober (11.5%, 7.6%, 7.1%, respectively). Genotyping of the beta-lactamase producing isolates revealed maximum possession of blaTEM followed by blaSHV and blaCTX-M. The nucleotide sequences were found similar with blaCTX-M-15, blaSHV-11, blaSHV-27, blaSHV-228, blaTEM-1 and blaAmpC in BLAST search. Distribution of studied biofilm associated genes in Enterobacteriaceae strains from different varieties of the birds revealed the maximum possession by layer birds followed by Vanraja, Desi, broilers, and Nicobari fowls. The phylogenetic analysis of selected sequences revealed a partial clonal relationship with human clinical strains of Indian subcontinent. Molecular docking depicted the Gibbs free energy release for 10 different macromolecules (proteins) and ligand (antibiotic) complexes, ranging from – 8.1 (SHV-27 + cefotaxime) to – 7 (TEM-1 + cefotaxime) Kcal / mol. Conclusion and relevance: The study revealed beta-lactamase variants circulating in the fowl population of Andaman and Nicobar Islands (India) even in remote places with low anthropogenic activity. Most of the strains possessed blaTEM-1, followed by blaCTX-M-15. Possession of blaSHV-11, blaSHV-27, blaSHV-228 in poultry Enterobacteriaceae strains was not reported earlier from any part of the globe. The phylogenetic analysis revealed a partial clonal relationship of beta-lactamase sequences with the human clinical strains isolated from Indian subcontinent.